Hubungan Antara Persepsi Terhadap Iklim Sekolah Dengan Etos Kerja Pada Santri Tahfidzul Qur'an - Sari, Wulan Purnama, Wisnu Sri Hertinjung, S.Psi, M.Psi, Psi (2016)
This research aims to know the level of perception of school climate, to know the level of work ethic and to know the effective contribution of the perception of school climate against work ethic. Researchers use quantitative methods to achieve the objectives of this research. The subject used in this research are the students of Class XI high school boarding schools Tahfidzul Qur'an (PPTQ) Ibnu Abbas Klaten. The result of the correlation coefficient (r) of 0.448 with the sig (2-tailed) = 0.000, p<0.01 shows there was a very significant positive relationships between the perception of school climate against work ethic at with students Tahfidzul Qur'an. Based on the results of the analysis variables work ethic have the empirical mean (RE) of 88,26 and the mean hypothetical (RH) of 77.5 which means the work ethic of research subject is high . The variable perception of school climate has the empirical mean (RE) of 75.58 and the mean hypothetical (RH) of 70 which means perception of school climate the subject of . The effective contributions perception of climate school 44,8 % of work ethic.